2002
DOI: 10.17221/5819-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of Escherichia coli O157 strains isolated from cattle and pigs by the use of PCR and pulsed-field gel electrophoresis methods

Abstract: ABSTRACT:Fourteen Escherichia coli O157 strains isolated from cattle and pigs in Poland and in Germany were investigated, using PCR, for the genetic markers associated with Shiga toxin-producing E. coli (STEC). Only two strains, both of cattle origin, were positive for the fliC (H7) gene and could be classified as O157 : H7. Nine isolates had stx shiga toxin genes, either stx1 (1 strain), stx2 (4 isolates) or both (4 strains). e stx2-carrying samples were further subtyped by PCR for the stx2c, stx2d, and stx2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…The degrees of genetic relatedness of swine STEC strains to strains from other animal species differed in those studies, and most studies focused on STEC O157:H7 (60,(69)(70)(71). Here, we found that STEC O59:H21 strains, which predominated in this swine population, were closely related among pigs in the same cohort.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…The degrees of genetic relatedness of swine STEC strains to strains from other animal species differed in those studies, and most studies focused on STEC O157:H7 (60,(69)(70)(71). Here, we found that STEC O59:H21 strains, which predominated in this swine population, were closely related among pigs in the same cohort.…”
Section: Discussionmentioning
confidence: 61%
“…Our study is the first one to use PFGE to analyze STEC strains recovered from repeated samples collected from pigs, while most of the previous studies used PFGE to determine the genetic relatedness of STEC strains from swine and other species (60,(69)(70)(71)(72). The degrees of genetic relatedness of swine STEC strains to strains from other animal species differed in those studies, and most studies focused on STEC O157:H7 (60,(69)(70)(71).…”
Section: Discussionmentioning
confidence: 99%
“…E. coli O157 or E. coli O157: H7 isolates obtained from cattle carcasses or feces have also been found to contain at least one of the stx1 , stx2 , eaeA , hylA and fliC h7 genes [5,7,22,25,29,35,38,39,41]. In contrast to other countries, there has been only one study of carcasses reported in Turkey [21].…”
Section: Discussionmentioning
confidence: 99%
“…A Polish study reported that one swine STEC O157 strain clustered with STEC O157 strains from cattle at a similarity criterion of 80% based on PFGE patterns. The swine STEC O157 strain was from a weaned pig with diarrhea, and no other epidemiologic relationship was described between the swine and cattle STEC strains (Osek and Gallien, 2002).…”
Section: Molecular Epidemiology Of Swine Stecmentioning
confidence: 99%